Lexico-Grammatical Analysis of Alice's Adventure in Wonderland and Its Pedagogical Implication - Novita Sari Novita; Junaedi Setiyono; Tusino Tusino (Scripta : English Department Journal, 2021)
This study aims to reveal: (1) the translation differences between source language (SL) and target language (TL) of the human translator and the machine translator on the translation of the Indonesian subtitle of Alice’s Adventures in Wonderland Movie, (2) lexical difference in translation differences between source language (SL) and target language (TL), (3) grammatical difference in translation differences between source language (SL) and target language (TL) and (4) the advantages in examining the translation differences related to vocabulary and grammar teaching for the tenth grade students of senior high school. This study used a qualitative descriptive. The data were taken subtitles sentences because what the researchers analyzes is the form of written language. The source of the data was script by Linda Woolverton (SL), the Indonesian subtitle was translated by Pein Akatsuki (TL 1) and the second Indonesian translator was Google translate (TL 2). This study used the researchers as the main instrument for collecting, classifying, and analyzing the data. The researchers read the script of English and Indonesian subtitle of the Alice’s Adventures in Wonderland Movie. The results of the descriptive analysis show that there are 147 data of the translation. It reveals that: (1) the translation of this research are 114 data (78%) difference and 33 data (22%) no translation difference of Indonesian Subtitle of Alice's Adventures in Wonderland Movie, (2) in the translation differences (351 items) there are lexical differences (169 items), (3) whereas, the difference of translations are grammatical differences (182 items), (4) there are several advantages in improving students’ vocabulary skills, teaching grammar, and finding the vocabulary and grammar in a course book Bahasa Inggris.